If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -1y + -2z = 4 Solving 7x + -1y + -2z = 4 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'y' to each side of the equation. 7x + -1y + y + -2z = 4 + y Combine like terms: -1y + y = 0 7x + 0 + -2z = 4 + y 7x + -2z = 4 + y Add '2z' to each side of the equation. 7x + -2z + 2z = 4 + y + 2z Combine like terms: -2z + 2z = 0 7x + 0 = 4 + y + 2z 7x = 4 + y + 2z Divide each side by '7'. x = 0.5714285714 + 0.1428571429y + 0.2857142857z Simplifying x = 0.5714285714 + 0.1428571429y + 0.2857142857z
| y^2-y-20/2y^2-8y-64 | | by-9b^3=4by-15b^3 | | 5y+18=8y | | 21=-2x+57 | | g(r)=-1-7r(6) | | 12x(-6)= | | (x-5)8=72 | | 3x+29=140 | | ax-a^2=cx-c^2 | | 6x(4x-3y)+y(4x-3y)= | | 8-1/4b=5 | | (4y+3)=0 | | 8(5+X)=7(X-7) | | .15x=1200 | | 5x-4+5x=-44 | | 510x+3y=2.5 | | 3x+172=6x+175 | | 3x-2y+6z=9 | | 8X+(2X-1)=-29 | | -x+6y-9y=4 | | 8+4x=o | | 2x-c=d | | 2x^3-11x^2-4x=0 | | 3.5x=5.8 | | Tn=10n-4 | | 7-2(2x+1)=x-5 | | 2.50/0.5 | | 30=5(r/5-3 | | Y=4+4(8) | | (5/3x)^2-(13/3x)-2=0 | | 0.5/2.50 | | (9x-9)+4=76 |